Corbynism from Below - Perryman, Mark, 1959- (Book collections on Project MUSE., 2019)
Jeremy Corbyn is the epitome of the anti-leader: he would, by impulse, shy away from the very idea of 'Corbynism'. Yet when a general election is called, Corbyn's Labour promises to force a break with the current consensus every bit as historic as those of Attlee in 1945 and Thatcher in 1979. Corbyn is a phenomenon that has been purposely misrepresented and wilfully misunderstood, with supporters derided as 'Corbynistas', fans and cultists. This book of specially commissioned essays explores the true nature of Jeremy Corbyn's leadership; expectations of how Labour might fulfil its promise of a new kind of politics; and the limits to what Labour can achieve; as well as offering tools for transforming the party from the bottom up. Building on the work of Mark Perryman's previous book The Corbyn Effect, this new collection is vital reading for all those interested in left politics and the future of the Labour Party. It presents a comprehensive account of Jeremy Corbyn's Labour Party: where it came from, how it has begun a process of radical change, and the party it promises to become.